Inorganic Fertilization Substitution in Mustard Plant (Brassica juncea L.) Through the Application of Goat Manure Liquid Organic Fertilizer - Kholifatul Fuadah; Anggi Indah Yuliana; Mohamad Nasirudin (AGARICUS: Advances Agriculture Science & Farming, 2026)
This study examines the impact of the application of inorganic fertilizer and goat manure liquid organic fertilizer on the growth and yield of mustard greens (brassica juncea L). In this study using a factorial random group design (RAK), there are two factors used. The first factor is the application of chemical fertilizers which are divided into three categories; A0 (without chemical fertilizer), A1 with a dose of 4 grams per plot (100%), and A2 with a dose of 2 grams per plot (50%). The second factor is the provision of goat manure poc; K0 (without POC), K1 (50 ml/L), K2 (100 ml/L) and K3 (150 ml/L). The data collected was analyzed through ANOVA to understand the significant differences between treatments, then continued with testing to determine the Smallest Real Difference (BNT) at the level of 5%. The results of the study showed that the use of inorganic fertilizers had an impact on the number of leaves, leaf area, dry weight, and fresh weight of the plant, where the A2 treatment with a dose of 50% gave better results than other treatments. Meanwhile, the POC effect of goat manure plays a role in determining plant height, number of leaves, leaf area, dry weight, and fresh weight, where the K2 treatment shows better results than other treatments. The interaction between inorganic fertilizer and goat manure POC significantly affected the accumulation of plant biomass at 21 days postplanting (HST), with A2K2 treatment (50% inorganic fertilizer + 100 mL/l POC) resulting in the highest dry weight compared to other treatments. Treatments that applied entirely inorganic fertilizers (A1) combined with POC at doses of 100 ml/L (A1K2) or 150 ml/L (A1K3) showed dry weight that did not show a significant difference when compared to treatments using 100% inorganic fertilizers without POC (A2K0). Therefore, the use of POC provides an opportunity to reduce the dose of inorganic fertilizers by up to 50% in caisim plants.